2017
DOI: 10.1155/2017/9243161
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Chronic Illness: Experiences of Iranian Families of Persons with Multiple Sclerosis—A Qualitative Study

Abstract: Background Today family members are providing care and support to each other during illness. In particular, in chronic illness, such as multiple sclerosis, the families are more involved in caring for and supporting their patients, so they use several strategies to cope with this situation. The purpose of this study was to explore the coping strategies in family caregivers of persons with multiple sclerosis in Iran. Methods This is a qualitative study that was conducted through 18 family caregivers of persons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 39 publications
1
29
0
Order By: Relevance
“…These requirements not only affect the patient but also the entire family, 4 who has a fundamental role in patients' adherence 5 . For married patients with chronic diseases, studies usually point to the spouse as the primary source of support and care 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…These requirements not only affect the patient but also the entire family, 4 who has a fundamental role in patients' adherence 5 . For married patients with chronic diseases, studies usually point to the spouse as the primary source of support and care 6,7 …”
Section: Introductionmentioning
confidence: 99%
“…46,47 The high cost of medication, the unavailability of some medication, the fear that their patients may lose their jobs, and lack of support from the government increase the stress which MS patients' families experience and make them search for other sources of support. 48 The participants were concerned about the possible progression of the disease in the future and the possible impact of atrophy caused by the disease on their lives; thus, their need for emotional support to cope with their crisis. Social support, especially from their friends and relatives, also can help them cope with their situation.…”
Section: Discussionmentioning
confidence: 99%
“…The illness of one family member can influence the life of the whole family and make them worry about the other members. Families are expected to be in the front line of support for patients; 11 however, in the hospital environment, most family caregivers feel abandoned in the process of providing care to their patients and their prolonged involvement in care can result in the dissatisfaction of the patients and their families with hospital care. 12 …”
Section: Introductionmentioning
confidence: 99%
“…They showed that patients with anxiety and depression were more likely to use negative adjustment and had unorganized religion. (29) Strong relationship between family members in the Iranian society help them to care for their patients in case that one of their family members became ill. (30) Religious coping help people to endure difficulties and prevent anxiety. Prayers, reciting Quranic verses, or attending religious ceremonies help religious people to be less vulnerable to stressful life events.…”
Section: Discussionmentioning
confidence: 99%
“…They showed that patients with anxiety and depression were more likely to use negative adjustment and had unorganized religion. ( 29 ) Strong relationship between family members in the Iranian society help them to care for their patients in case that one of their family members became ill.( 30 )…”
Section: Discussionmentioning
confidence: 99%